THE INFLUENCE OF CONTENT MARKETING AND ELECTRONIC WORD OF MOUTH ON PURCHASE INTENTION AND ALSO BRAND IMAGE AS MEDIATION - Amarta, Tasya; Sidharta, Helena (Universitas Ciputra Surabaya, 2024)
The purpose of this research is to find out how content marketing and electronic word of mouth influence purchase intention and also brand image as mediation. The sampling technique uses purposive sampling using several criteria. The researcher has collected data with the total of 200 respondents from potential HMNS customers on the Instagram social media page @hmns.id. This research uses quantitative approach by using SEM PLS data analysis method that is assisted by smart PLS 4.0 software. Based on the results of the analysis that has been carried out, it shows that content marketing has a significant positive effect on purchase intention, electronic word of mouth has a significant positive effect on purchase intention, content marketing has a significant positive effect on brand image, electronic word of mouth has a significant positive effect on brand image, brand image has a significant positive effect on purchase intention, and content marketing has a significant positive effect on purchase intention mediated by brand image, and electronic word of mouth has a significant positive effect on purchase intention mediated by brand image. In conclusion, this study accepts all the hypotheses proposed.